Zustand der Grundfischbestände der Kieler Bucht im Jahre 1967 - Thurow, F. (1968)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010